Stylistics - Bradford, Richard (Routledge., 1997)
Richard Bradford provides a definitive introductory guide to modern critical ideas on literary style and stylistics. It will provide students with a basic grasp of stylistics and literary analysis. This comprehensive and accessible guidebook for undergraduates examines: * the terminology of literary form * how literary style has evolved since the sixteenth century * the role of stylistics in twentieth century criticism * the discipline of stylistics from classical rhetoric to post-structuralism * the relationship between literary style and its historical context * style and gender * examples of poems, plays and novels from Shakespeare to the prese